Efektivitas Project-Based Learning dalam Meningkatkan Pemahaman Konsep Bangun Datar 2D Matematika di Kelas V Sekolah Dasar - Rahayuningsih, Setiti; Pantiwati, Yuni (Jurnal PGSD, 2025)
This research aims to analyze the impact of implementing the Project-Based Learning (PjBL) approach on enhancing fifth-grade students' understanding of plane figure perimeter concepts at SD Muhammadiyah 4 Malang. Employing a quantitative method with a pretest-posttest design without a control group, data were collected through written tests and project-based evaluations using an assessment rubric. The findings revealed a significant improvement in the students’ average posttest score compared to the pretest score, indicating that the PjBL approach effectively increased conceptual understanding (p < 0.05). Item analysis showed that the difficulty index fell within the moderate category (0.5–0.8), with most items demonstrating good discrimination power (above 0.3). The instrument's reliability, indicated by Cronbach’s Alpha, was 0.903, reflecting excellent internal consistency. Project assessment results recorded an average score of 91.2, categorized as "Very Good," which shows that students were able to creatively and collaboratively apply the perimeter concept to real-life contexts. These outcomes demonstrate that PjBL effectively promotes students' conceptual understanding while simultaneously supporting the development of essential 21st-century skills.